Project Management in Construction, Seventh Edition - Levy, Sidney M. (McGraw-Hill Education, 2018)
Provides all of the information necessary to efficiently execute every phase of any construction job. The book features complete details on estimating, purchasing, contract administration, team management, quality control and assurance, and other topics essential to completing a project on time and within budget. Project Management in Construction, Seventh Edition, covers new OSHA regulations and new contract formats that emphasize collaboration and teamwork.